Kebijakan manajemen resiko pada perbankan yang terancam likuidasi - Kartika, Fitrotul Candra (Maliki Interdisciplinary Journal, 2023)
Risk management policy is an important aspect of the success and sustainability of banking operations. Banks, as financial institutions, are vulnerable to various risks, including liquidity risks that can threaten their financial stability. Therefore, an effective risk management policy is needed to minimize risks and protect the stability of the financial system. The research method used in this study will involve a review of related literature, theoretical analysis, as well as a comprehensive case study. This research will collect data from various sources, including academic journals, books, research reports, and organizational case studies. The aim of this journal is to investigate risk management policies in banks that are threatened with liquidation. Overall, this article provides a valuable resource for anyone interested in financial management and risk management. By properly managing liquidity risk, banks can reduce threats to their liquidity and maintain stable operational continuity.